Cultural landscapes: Contributions in the field of Mexican Microhistory and environmental management - Romero, Jose Feliciano Perez (Seven Editora, 2023)
This work is part of the preliminary advances made within the framework of the doctoral research project called "Legal-administrative and socio-ecological analysis of the Los Tuxtlas Biosphere Reserve: the case of the Balzapote ejido". The object of this essay is to enunciate how the cultural landscape is analyzed and described from various Mexican perspectives committed to recovering the socio-historical-environmental processes that reconfigured part of the Mexican rural territory. For this, first, as an introduction, the theoretical approaches of Mexican microhistory and environmental management proposed by the authors Luis González and González & Raúl Brañes Ballesteros are disrupted; subsequently, based on these statements, some contributions made in cultural landscapes of the Mexican territory are exposed; from the Tuxtlas region; and, from the common Balzapote. Finally, the text concludes with some reflections on the disciplinary approaches, the dimensions of analysis, and the techniques that prevailed for data collection in the works examined. DOI:https://doi.org/10.56238/devopinterscie-256